The health fair model for surveillance of non-communicable disease: a pilot study in St. Kitts. (2020) - Kungurova, Yulia; Satyadev, Nihal; Flores, Nicole De Leon; Ndrio, Mariana; Lad, Aumkar; Desai, Vidhi; Sholl, Kristen; Le, Ngoc; Benson, Elizabeth; Goodwin, Raven; Flint, Jesica; Kuhnkuhn, Surpreet; et al.
No abstract available